Methods of treatment of postnecroctic pancreatic cysts: modern looks of the problem (literature review) - I. G. Noskov (Acta Biomedica Scientifica)
Choosing a surgical method of treatment of postnecrotic pancreatic cysts is an extremely urgent problem these days. With developing technologies and increasing number of minimally invasive methods of treatment, diagnostic capabilities tend to improve. Whereas traditional methods of surgical treatment do not lose their relevance, recent studies optimize the indications for their implementation, which in turn reduces the frequency of the nearest and distant postoperative complications. The article deals with the questions of conservative therapy of postnecrotic cysts, indications and choice of a method of surgical treatment. It covers the methods of minimally invasive surgery, the application of which allows achieving excellent clinical results of treatment The authors pays particular attention to the recent tendency of using several methods of minimally invasive treatment describing that the combination of minimally invasive internal and external drainage has shown its effectiveness. It should be noted that performing intervention data from the position of pathogenetic treatment helps to achieve a good clinical result. The data on the success of combined drainage of postnecrotic cysts are few, which requires confirmation by a large number of publications. Thus, the high incidence of acute pancreatitis, the lack of diagnostic algorithms and clear indications for a wider range of existing methods of surgical treatment of postnecrotic pancreatic cysts leaves a field for subsequent studies and observations.